Effects of wood ash, green residues and N-free fertiliser on naturally regenerated birch and field vegetation in a young Norway spruce stand in SW Sweden. Issue 5 (4th July 2021) - Brandtberg, Per-Olov; Wang, Pei; Olsson, Bengt A.; Arvidsson, Helen; Lundkvist, Helene
ABSTRACT : Treatments added to young conifer stands aiming to compensate for the loss of nutrients and alkalinity associated with whole-tree harvesting for bioenergy purposes have the potential to affect the growth of competitors to the conifers. Three different nutrient compensation treatments were applied to a young Picea abies (L.) Karst. stand in south-west Sweden, 2 or 3 years following final felling. The treatments were; fine fraction of harvest residues (15 Mg dw ha −1 ); granulated wood ash (4.1 Mg dw ha −1 ); nitrogen-free vitality fertiliser (twice 1.5 Mg ha −1 ); untreated control. Root biomass and total biomass of graminoids (mainly Deschampsia flexuosa (L.) Trin) were significantly greater in the wood ash and vitality fertiliser treatments than in the residues and control treatments. The aboveground and coarse root biomass of naturally regenerated birch ( Betula spp.) and the aboveground biomass of dwarf shrubs (mainly C alluna vulgaris (L.) Hull.) and bottom layer were not affected by the treatments. Calcium and magnesium concentrations in the aboveground biomass of graminoids and phosphorus concentration in the biomass of bottom layer were significantly the highest in the vitality fertiliser treatment. Thus, nutrient compensation with vitality fertiliser or granulated wood ash may increase competition from graminoids in the establishment phase.